Spontaneous expression of the interleukin 2 receptor gene and presence of functional interleukin 2 receptors on T lymphocytes in the blood of individuals with active pulmonary sarcoidosis. - Konishi, K (1988)
Current concepts of the pathogenesis of sarcoidosis suggest that the expanded numbers of activated T-helper/inducer cells at sites of disease activity result, at least in part, from their proliferation in the local milieu. Normal clonal proliferation of T cells involves activation and expression of the IL 2 receptor (IL 2R) gene. Thus, knowing that IL 2R mRNA transcripts are relatively long lived, we hypothesized that sarcoid blood T cells may contain IL 2R mRNA transcripts and express functional surface IL 2R, although the cells are probably activated elsewhere. Northern analysis using a 32P-labeled cDNA probe for the IL 2R p55 protein demonstrated that blood T cells of patients with active sarcoidosis, but not of normal patients, express 3.5- and 1.5-kb IL 2R mRNA transcripts, the same as those observed in normal T cells activated in vitro. Consistent with this, using flow cytometry and an MAb directed against the IL 2R p55 protein (2A3), we observed detectable levels of IL 2R surface protein on increased numbers of blood T cells of active sarcoidosis patients (4.7 +/- 0.9%) compared with blood T cells of normal patients (0.9 +/- 0.2%). Importantly, when the sarcoid blood T cells were exposed to IL 2 in vitro, they proliferated at a rate greater than that of normal blood T cells under the same conditions, suggesting that the IL 2R spontaneously expressed by sarcoid blood T cells were functionally active. In the context of the known compartmentalization of spontaneous IL 2 production and T cell proliferation at sites of disease in active pulmonary sarcoidosis, these IL 2R positive blood T cells would probably have a proliferative advantage if they trafficked to sites of active sarcoidosis, such as the lower respiratory tract.